Discovery of two highly divergent negative-sense RNA viruses associated with the parasitic nematode, Capillaria hepatica, in wild Mus musculus from New York City. (12th October 2019) - Williams, Simon H.; Che, Xiaoyu; Oleynik, Alexandra; Garcia, Joel A.; Muller, Dorothy; Zabka, Tanja S.; Firth, Cadhla; Corrigan, Robert M.; Briese, Thomas; Jain, Komal; Lipkin, W. Ian
Abstract : Recent advances in high-throughput sequencing technology have led to a rapid expansion in the number of viral sequences associated with samples from vertebrates, invertebrates and environmental samples. Accurate host identification can be difficult in assays of complex samples that contain more than one potential host. Using unbiased metagenomic sequencing, we investigated wild house mice ( Mus musculus ) and brown rats ( Rattus norvegicus ) from New York City to determine the aetiology of liver disease. Light microscopy was used to characterize liver disease, and fluorescent microscopy with in situ hybridization was employed to identify viral cell tropism. Sequences representing two novel negative-sense RNA viruses were identified in homogenates of wild house mouse liver tissue: Amsterdam virus and Fulton virus. In situ hybridization localized viral RNA to Capillaria hepatica, a parasitic nematode that had infected the mouse liver. RNA from either virus was found within nematode adults and unembryonated eggs. Expanded PCR screening identified brown rats as a second rodent host for C. hepatica as well as both nematode-associated viruses. Our findings indicate that the current diversity of nematode-associated viruses may be underappreciated and that anatomical imaging offers an alternative to computational host assignment approaches.